A Systematic Literatur Review of Change Leadership: Mediation – Moderation Model - Sri Kurnia Abdi Pradhana; Muhammad Fakhruddin Mudzakkir (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study examines change leadership through a systematic literature review of 40 journals spanning the past 10 years, focusing on antecedent, consequence, mediating, and moderating variables in various organizational contexts. Antecedent variables include leader characteristics, organizational culture, and follower dynamics, which form the foundation for successful change leadership. The resulting consequences include positive impacts on individuals, such as increased job satisfaction, intrinsic motivation, and reduced stress, and organizational benefits, such as increased innovation, effectiveness, and change management. Mediating variables, such as work motivation and organizational trust, and moderating variables, such as organizational culture and resistance to change, play a significant role in influencing the relationship between change leadership and outcomes. The study also highlights that the health, education, and technology sectors are the main focus, with the geographical distribution reflecting both developed and developing country contexts. In conclusion, Change Leadership has a significant impact on the success of organizational transformation, with effectiveness influenced by various contextual, individual, and organizational variables, thus providing important insights for practitioners and academics in understanding the critical dimensions of change leadership.